Co-creating sustainable futures: A biogas case study in Argentina's humid pampas - Echarte, María Mercedes (2026)
Rural development in Argentina demands comprehensive solutions that address social, environmental, and cultural factors, in addition to economic ones. Decades of unreliable energy supply, deficient infrastructure and services, declining rural labor demand, and environmental pollution from inadequately treated agricultural and agro-industrial waste have led to rural depopulation. This study examines how rural cooperative bioenergy initiatives might emerge and evolve during early-stage implementation under conditions of institutional volatility, using the Los Pinos Biogas Demonstration Unit (BDU) as a qualitative case study. Through a transdisciplinary, participatory process involving researchers, local government, private companies, and community members, a cooperative-managed biogas plant was designed and constructed to address the local energy and environmental challenges faced by a small rural town in the Humid Pampas. The experience is interpreted as a formative socio-technical process characterized by partial institutionalization, in which participatory governance and technological learning advanced despite persistent regulatory, financial, and market constraints. Integrating innovation ecosystem and business environment perspectives, the study shows how local collaboration, adaptive learning, and social embedding can coexist with structural barriers that limit consolidation and replicability. The paper provides analytical grounded insights into the conditions shaping community-based bioenergy initiatives and highlight the need for bioeconomy policies that better align institutional stability, local autonomy, and inclusive governance, particularly in developing-country contexts.